Hofmeister Effect in RT-QuIC Seeding Activity of Chronic Wasting Disease Prions - Hwang, Soyoun; Beckley, Danielle; Alekseev, Konstantin P.; Nicholson, Eric M. (Frontiers in Bioengineering and Biotechnology, 2021)
Chronic wasting disease (CWD) is a transmissible spongiform encephalopathy (TSE) that causes a fatal neurodegenerative disease in cervids. Cases of CWD are rapidly increasing in North America among wild and farmed cervid populations, and potential for zoonotic transmission is not yet determined. Therefore, in order to manage the disease, it is imperative to devise a system that can detect CWD during its early phases to prevent spread to new captive herds through introduction of CWD affected animals into otherwise CWD free herds. Real-time quaking-induced conversion (RT-QuIC) assays have been applied to detect the presence of disease associated prions from various samples in both animals and humans. In this study, we have tested the use of five Hofmeister anions that range from weakly hydrating to strongly hydrating: Na3Citrate, Na2SO4, NaCl, NaI and NaClO4 in RT-QuIC reactions for CWD seeding activity using different recombinant prion proteins as substrates. This work shows how the ionic environment of the RT-QuIC reaction can enhance or diminish the seeding activity. Selection of the proper ion environment and recombinant prion protein substrate will make RT-QuIC a powerful diagnostic tool for early detection of CWD prions, further supporting CWD surveillance in wild and captive cervids.